Beneficial Effect of Endovascular Therapy and Low‐Density Lipoprotein Apheresis Combined Treatment in Hemodialysis Patients With Critical Limb Ischemia due to Below‐Knee Arterial Lesions. Issue 6 (14th July 2016) - Ohtake, Takayasu; Mochida, Yasuhiro; Matsumi, Junya; Tobita, Kazuki; Ishioka, Kunihiro; Oka, Machiko; Maesato, Kyoko; Moriya, Hidekazu; Hidaka, Sumi; Saito, Shigeru; Kobayashi, Shuzo
Abstract: To assess the clinical benefit of combined treatment of below‐knee endovascular therapy (BK‐EVT) plus low‐density lipoprotein apheresis (LDLA) compared with BK‐EVT monotherapy, we retrospectively evaluated the clinical outcome of hemodialysis (HD) patients with critical limb ischemia (CLI) due to isolated BK arterial lesions who underwent BK‐EVT or BK‐EVT plus short‐term LDLA. Between October 2011 and September 2014, 62 HD patients underwent isolated BK‐EVT monotherapy (BK‐EVT group), and 25 HD patients underwent BK‐EVT plus LDLA (BK‐EVT + LDLA group). LDLA was started within 1 week after BK‐EVT and performed four times in total within next 2 weeks. Major adverse limb events (MALE) including major amputation and re‐intervention, and all‐cause mortality were examined by Kaplan–Meier method and the log‐rank test. Baseline characteristics were not different other than low ABI and low dorsal SPP in BK‐EVT + LDLA group. Cumulative MALE‐free rate was significantly improved in BK‐EVT + LDLA group over the BK‐EVT group (72.0% and 45.1% respectively at 30 months after treatment, P =  0.04). All‐cause mortality did not differ between the two groups. Major causes of death were heart failure and sepsis in both groups. Short‐term LDLA hybrid treatment immediately after BK‐EVT might improve the outcome of ischemic limbs after re‐vascularization therapy.